The 1596 Keicho Earthquake, a 5‐Day, 300‐km‐Long Sequential Rupture Event in the Median Tectonic Line Fault Zone, Southwestern Japan. Issue 8 (5th August 2019) - Ikeda, Michiharu; Toda, Shinji; Onishi, Kozo; Nishizaka, Naoki; Suzuki, Shunsuke
Abstract: Historical accounts and geological surveys suggest that a sequential rupture event occurred in 1596 CE in the Median Tectonic Line fault zone (MTLFZ) in southwestern Japan. During this event, known as the 1596 Keicho earthquake, the rupture probably propagated in two or three sequential stages, similar to a series of events that occurred along the North Anatolian fault during 1939–1999. The detailed rupture process of the 1596 earthquake event is unknown, however, because coseismic seismological, geological, and geodetic observation data are not available. To reconstruct the rupture processes, we integrated data from Coulomb stress change analyses, fault geometrical analyses, historical accounts, and rupture history. The results suggest that the rupture initiated on the Kawakami fault on 1 September 1596 and propagated bilaterally, to the Beppu Bay fault system, which ruptured on 4 September, and to the MTLFZ in eastern Shikoku and the Rokko‐Awaji fault zone and Arima‐Takatsuki Tectonic Line in the Kinki area, which ruptured on 5 September. However, there is a small possibility that the rupture initiated at the western end of the MTLFZ and propagated eastward unilaterally. The propagation of ruptures might be sensitively controlled not only by stress perturbation and fault geometry but also by rupture history. Evaluation of fault rupture behavior from various viewpoints can contribute to the mitigation of future seismic disasters in fault zones where detailed coseismic observation data from the past are lacking. Key Points: Coulomb stress change analyses might provide important information to estimate the rupture scenario of a historical rupture event Fault rupture history regional stress conditions and fault geometry might contribute to triggering rupture of neighboring faults Our results indicate that the 1596 Keicho earthquake likely initiated on the Kawakami fault and that the rupture propagated bilaterally